Manajemen Kesiswaan Berbasis Pembinaan Karakter Islami pada Madrasah Ibtidaiyah - Hamdanah, Hamdanah (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2023)
This study aims to analyze the implementation model of Islamic character-based student management in Madrasah Ibtidaiyah, describe student behavior management strategies, and examine its impact on student achievement. The research employs a qualitative approach with an instrumental case study design. Research subjects include madrasah principals, teachers, students, and parents selected through purposive sampling technique. Data collection was conducted through in-depth interviews, participant observation, documentation, and focus group discussions. Data analysis utilized the Miles, Huberman, and Saldaña model with stages of data condensation, data display, and conclusion drawing. Data validity was ensured through source, method, and time triangulation, as well as member checking. The findings reveal that student management implementation follows a cyclical model integrating Islamic values in planning, organizing, implementing, and evaluating. Behavior management strategies include habituation, role modeling, advising, positive reinforcement, logical consequences, and parent collaboration, with role modeling being the most effective strategy. Supporting factors include leadership commitment, teacher competence, and parental support, while inhibiting factors encompass time constraints, diverse family backgrounds, and social media influence. Positive impacts are evident in spiritual-moral achievement (85% of students regularly perform worship, 60% reduction in violations), academic achievement (12-15 point increase in grades, 100% graduation rate), and non-academic achievement. This study concludes that Islamic character-based student management effectively shapes students' personalities holistically while enhancing multidimensional achievement